(untitled) (Research, Society and Development, 2020)
The aim of this study was to assess the genotoxic and antigenotoxic effects of Poincianella bracteosa bark aqueous extract on DNA damage induced by doxorubicin (DXR) a chemotherapeutic agent using SMART (Somatic Mutation and Recombination Test). The analysis was performed using the somatic mutation and recombination test in Drosophila melanogaster. Larvae from the standard and high-bioactivity crosses were chronically treated with four concentrations of P. bracteosa bark tea, alone and in association with DXR. The results revealed no mutagenic effect of bark extract for any of the concentrations tested. A modulating effect of aqueous extract in reducing the genotoxic action of DXR was observed for all concentrations tested in descendants of both crosses, but inhibition was more effective in those from the high-bioactive cross. The modulating effect observed may be associated with the presence of tannins and reducing sugars, as observed in phytochemical studies, since they are capable of capturing and stabilizing free radicals. Given the widespread use of P. bracteosa bark in folk medicine, further studies to elucidate the mechanism of action of these cellular compounds and with other experimental models would be useful to confirm that P. bracteosa extract is beneficial to human health.